Alternative procedure to determine the response reduction factor for ductile rc framed buildings (Gaceta Técnica, 2018)
The seismic design is based on the results of the structures elastic analysis, even though now days the nonlinear analysis is increasingly accessible. To perform the seismic analysis of structures that are modeled with elastic behavior, but known to venture into the plastic behavior, the standards establish the reduction of the elastic design spectra by the use of reduction factors, formulated essentially on the basis of the engineering judgment. This paper proposes a strategy to obtain response reduction factors, based on the results of non-linear analysis of soil response and structural systems with a degree of freedom, along with the non-linear response of multiple grade of freedom framed structural systems by armed concrete, for the specific spectra of Venezuela. The results of response reductions factors were greater than the current values of response reduction prescribed by the Venezuelan seismic code, which can favorably lead to a displacement-based design instead strength-based design.
Keywords: design spectrum; response reduction factor; non-linear analysis